The Role of Strategic Lens to Achieving Organizational Prosperity: (An Analytical Study for Managers Opinions in a Housing Sector Organizational / Kurdistan Region- Iraq) - حمدي سعيد البروشكي, هيفي; خليل إسماعيل, هادي (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The current research aims to diagnose the role of the strategic lens in achieving organizational prosperity. Where a questionnaire was adopted to collect data through a comprehensive survey of the research community, and the final number of respondents reached (282) managers in the housing sector organizations / Kurdistan Region, and statistical analysis of the data was conducted using the statistical software (SPSS version 22), correlation coefficient and linear regression analysis were used to test hypotheses. The field study proved that respondents agreed on a high degree of practicing the dimensions of the strategic lens combined (stakeholder participation, resource mobilization, knowledge development, and organizational culture management) and the dimensions of organizational prosperity combined (creativity, intellectual capital, and sustainable competitive advantage) in the surveyed organizations(.It also proved the existence of a significant effect of the strategic lens on organizational prosperity at the level of the overall indicator and at the level of dimensions. Based on the conclusions, a number of proposals were presented to enhance the level of adoption of the strategic lens by the surveyed organizations, and to enhance the level of organizational prosperity in them.